2000
DOI: 10.1080/10473289.2000.10464134
|View full text |Cite
|
Sign up to set email alerts
|

A Fabric Denuder for Sampling Semi-Volatile Species

Abstract: A new style of diffusion denuder has been evaluated specifically for sampling HNO 3 . A coated fabric is used as the denuder substrate, which can be loaded directly into a standard filter holder. This approach allows direct denuder sampling with no additional capital costs over filter sampling and simplifies the coating and extraction process.Potential denuder materials and coatings were evaluated in the laboratory to test the removal efficiency. NaCl coatings were used to assess more than 20 materials for HNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Negative NO 3 Ϫ sampling artifacts are also common. 12,13,[25][26][27][28][29][30][31][32][33] Loss of NH 4 NO 3 as a result of changing ambient conditions (e.g., T, RH, and/or gas phase concentrations of NH 3 or HNO 3 ) during a sampling interval can lead in some cases to significant biases in measured NO 3 Ϫ concentrations. Such losses can be reduced by shortening sample periods, reducing filter face velocities, and limiting filter pressure drops, 34 but they remain problematic.…”
Section: Nitrate (Nomentioning
confidence: 99%
“…Negative NO 3 Ϫ sampling artifacts are also common. 12,13,[25][26][27][28][29][30][31][32][33] Loss of NH 4 NO 3 as a result of changing ambient conditions (e.g., T, RH, and/or gas phase concentrations of NH 3 or HNO 3 ) during a sampling interval can lead in some cases to significant biases in measured NO 3 Ϫ concentrations. Such losses can be reduced by shortening sample periods, reducing filter face velocities, and limiting filter pressure drops, 34 but they remain problematic.…”
Section: Nitrate (Nomentioning
confidence: 99%
“…Fabric denuders were first evaluated by looking at the removal efficiency of HNO 3 by sodium carbonate-coated examples. 26 Fitz and Motallebi observed that they could estimate denuder efficiency by estimating the fractional penetration of the gas and assume that the denuder is treated with a chemical that quantitatively removes a target gas when the gas in question comes in contact with the denuder surface. 26 They concluded that two denuders made of a cotton fabric, 47 mm in diameter, were required in series to ensure a collection of more than 95% of the HNO 3 in ambient air when sampling up to 10 L/min.…”
Section: Methodsmentioning
confidence: 99%
“…25 Fitz and Motallebi recently reported the successful use of fabric denuders to selectively remove HNO 3 . 26 The denuder sampling approach they proposed is based on diffusion batteries to remove very fine particles. The use of cloth fabric as the denuder substrate is analogous to the wire screen denuders for collecting very fine particles in diffusion batteries.…”
Section: Methodsmentioning
confidence: 99%
“…The fabric denuder has a relatively small loading capacity and suffers from significant particle loss (Fitz and Motallebi, 2000). Tsai et al (2001) developed a personal porous-metal denuder specifically for adsorbing acidic gases and ammonia gas in an occupational environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, these denuders are connected to an Ion Chromatography (IC) system or other sizeable infrastructure which makes them infeasible for personal sampling. Proposed by Fitz and Motallebi (2000), the fabric denuder is another type of new denuder. Fabric filter paper is coated and loaded in a filter stack, and collected pollutants are extracted in the same way as common filters.…”
Section: Introductionmentioning
confidence: 99%